A new type of glutathione-responsive anti-osteosarcoma prodrug nanoparticles. (29th July 2022) - Zheng, Yangfan; Ye, Jia; Zhang, Zhirong; Li, Lewei; Yu, Hongyuan; Wang, Siyi; Shen, Simin; Zhang, Qiufang; Zhang, Wei; Tao, Xiaojun; He, Chunlian
ABSTRACT: In this study, we grafted hydrophilic γ-polyglutamic acid (γ-PGA) with the hydrophobic drug methotrexate (MTX) to develop an amphiphilic and stimuli-responsive nanoparticles (MTX-SS-PGA NPs). The average size and zeta potential for MTX-SS-PGA NPs were 100.5 nm and −20.4 mV. In vitro drug release, the MTX cumulative release of nanoparticles within 72 h, which was more robust at 10 mM GSH (90.1%) than normal physiological environment pH 7.4 (9.8%). The disulphide bond was easily cleaved by glutathione, which subsequently led to the disintegration of the nanoparticle structure and the release of MTX. In cell studies, 10 μM MTX-SS-PGA NPs was efficient taken up into the cancer cell, released MTX in a redox-responsive manner, and exhibited cytotoxicity as potent as MTX.Moreover, 10 μM MTX-SS-PGA NPs have little side effects on normal cells. Overall, this new type of glutathione-responsive anti-osteosarcoma prodrug nanoparticles is promising for efficient drug delivery.